2001
DOI: 10.1074/jbc.m103237200
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived Neurotrophic Factor Enhances Neuronal Translation by Activating Multiple Initiation Processes

Abstract: The effects of neurotrophic factors on translational activation were investigated in cortical neurons. Brainderived neurotrophic factor (BDNF) increased protein synthesis within 30 min, whereas insulin produced a weaker enhancement of protein synthesis. BDNF-triggered protein synthesis was inhibited by LY294002, PD98059, and rapamycin, whereas the effect of insulin was unaffected by PD98059. To explore the mechanisms underlying this effect, the protein phosphorylation cascades that lead to the activation of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
190
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 54 publications
(66 reference statements)
10
190
1
2
Order By: Relevance
“…eIF4E was shown to play a pivotal role in the activation of translation by epidermal growth factor and nerve growth factor in PC12 cells after nutrient deprivation (23). In cortical cultures, brain-derived neurotrophic factor is a better stimulator of protein synthesis than insulin because it phosphorylates eIF4E, whereas insulin does not (25). In a similar manner, eIF4E phosphorylation by TGF-␣ might be involved in the recovery of protein synthesis after NMDA exposure.…”
Section: Tgf-␣ Promotes Protein Synthesis Recovery and Eif4ementioning
confidence: 80%
See 2 more Smart Citations
“…eIF4E was shown to play a pivotal role in the activation of translation by epidermal growth factor and nerve growth factor in PC12 cells after nutrient deprivation (23). In cortical cultures, brain-derived neurotrophic factor is a better stimulator of protein synthesis than insulin because it phosphorylates eIF4E, whereas insulin does not (25). In a similar manner, eIF4E phosphorylation by TGF-␣ might be involved in the recovery of protein synthesis after NMDA exposure.…”
Section: Tgf-␣ Promotes Protein Synthesis Recovery and Eif4ementioning
confidence: 80%
“…Under the phosphorylated state, they dissociate from eIF4E and no longer block the complex formation. The mammalian target of rapamycin, a downstream kinase of Akt (18), is the enzyme responsible for eIF4E-BP phosphorylation in cortical neurons (25). Many growth factors, such as IGF-1 (26), brain-derived neurotrophic factor (25), and epidermal growth factor (55) activate the mammalian target of rapamycin and phosphorylate eIF4E-BP.…”
Section: Tgf-␣ Promotes Protein Synthesis Recovery and Eif4ementioning
confidence: 99%
See 1 more Smart Citation
“…Rapamycin-sensitive signaling has been shown to be involved in BDNF-mediated activation of translational factors and increases in selected proteins. Takei et al (2001) showed that BDNF induces the expression of phospho-4E-BP1 and phospho-eIF4E in cortical neurons, and that this effect can be blocked by RAP. A related study found that RAP also attenuated the BDNF-induced expression of Arc and CamkII protein in cortical neurons (Takei et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no study has documented effects of rapamycin on neuronal gene transcription. Rapamycin mediates protein synthesis stimulated by brain derived neurotrophic factor (Takei et al, 2001;Schratt et al, 2004). Rapamycin has also been shown to have direct neurophysiological effects, although some of the data have been controversial.…”
Section: Introductionmentioning
confidence: 99%